KEANEKARAGAMAN FENOTIPE DAN DAYA DUKUNG LINGKUNGAN PADA AYAM LOKAL DI KECAMATAN MERAWANG KABUPATEN BANGKA - Riko Irwanto; Marinah; Shalsabilla Rizqi Aulia Awanni; Tissya Milly Gusnia (PendIPA Journal of Science Education, 2023)
The aims of this study were to determine the diversity of phenotypes and the status of environmental carrying capacity in local chicken cultivation in Merawang District, Bangka Regency. This research was conducted in 5 villages in Merawang District which have many local chicken coops. The sampling method used is purposive sampling. Data analysis was carried out by gender. The parameters observed in this study were phenotype observations in the form of qualitative characteristics (feather color, feather pattern, feather pattern, feather flickering, shark color and comb type) and quantitative traits (chicken body weight, chicken, chicken breast circumference, length of femur, shank length and environmental parameters). The results obtained were 164 local chickens. The chickens obtained consisted of 108 female chickens and 56 male chickens. The results showed the dominant comb shape was rose (male) and pea (female), feather color was white (male) and colored (female), yellow shank color, feather pattern for both males. and dominantly striated females. The dominant feather pattern is Colombia, while the flickering feathers are dominant for both local and female chickens. The results showed that the body weight of local chickens in five villages, Merawang District had an average of 12.6 ± 9.33 kg (male) and 192.4 ± 2.87 kg (female). Based on body size data, values in millimeters (mm) were obtained for males and females, such as body length 1.734 ± 51.53 and 3.091 ± 104.13; shank lengths 306.6±9.78 and 551.8±18.16; thigh (femur) length 749±28.53 and 1,403±46.74; calf length (tibia) 702±17.60 and 1,228±38.29; and shank circumferences 63.6 ±1.16 and 121±3.77. The average temperature of the cage during observation was 28ºC with feed given an average of three times a day, namely in the morning, afternoon and evening. Environmental factors such as housing and temperature become the carrying capacity of local chicken cultivation in Bangka.